MPLS-enabled applications : emerging developments and new technologies - Minei, Ina.; Lucek, Julian (Chichester : John Wiley & Sons, Ltd., 2010)
With a foreword by Yakov Rekhter. "Here at last is a single, all encompassing resource where the myriad applications sharpen into a comprehensible text that first explains the whys and whats of each application before going on to the technical detail of the hows.". -- Kireeti Kompella, CTO Junos, Juniper Networks. The authoritative guide to MPLS, now in its Third edition, fully updated with brand new material!. MPLS is now considered the networking technology for carrying all types of network traffic, including voice telephony, real-time video, and data traffic. In MPLS-Enabled Applic.
14 Advanced Protection and Restoration: Protecting the Service15 MPLS Management; 16 MPLS in Access Networks and Seamless MPLS; 17 MPLS Transport Profile (MPLS-TP); 18 Conclusions; Appendix A: Selected Backhaul Scenarios in MPLS-Based Access Networks; Appendix B:MPLS Resources; Appendix C: Solutions to Selected Study Questions; Appendix D: Acronyms; Index.
Includes bibliographical references and index.
Print version record.
Keywords: MPLS standard; Extranets (Computer networks); MPLS standard; Extranets (Computer networks); TECHNOLOGY & ENGINEERING -- Telecommunications; Extranets (Computer networks); MPLS standard; MPLS standard; Extranets (Computer networks); Electronic books